Sensory Evaluation from Asian Consumers of Six Different Beef Shank Cuts - W. Wu; E. A. Rice; B. A. Olson; T. G. O'Quinn; T. A. Houser; E. A. Boyle; M. D. Chao (Kansas Agricultural Experiment Station Research Reports, 2020)
Objective:The objective of this study was to evaluate factors affecting Asian consumers’ purchasing decisions and eating preferences of six different beef shank cuts. Study Description:Six different beef shank cuts, three from the forequarter [biceps brachii (shank A); a combination of deep digital flexor and flexor digitorum superficialis (shank B); extensor carpi radialis (shank C)], and three from the hindquarter [flexor digitorum superficialis (shank D); deep digital flexor (shank E); and a combination of long digital extensor, medial digital extensor and peroneus tertius (shank F)] were collected from 12 U.S. Department of Agriculture Low Choice beef carcasses. Shanks from the left side of the carcasses were used for consumer taste panels, and consumers visually evaluated size and surface color of samples from the right side of the carcasses. The BottomLine:There were differences among consumer preferences for different shank cuts. Consumers preferred shanks A, D, and F in the sensory taste panel, while shanks A and C were the most preferable in visual evaluation. Shanks A, D, and F should be priced with a premium, while shank C should be discounted in domestic Asian and international markets.
Keywords: beef shank; sensory panel; consumer